Maternal occlusal disharmony during pregnancy induces spatial memory deficits associated with the suppression of hippocampal neurogenesis in adult mouse offspring. Issue 1 (April 2017) - Kondo, Hiroko; Uchida, Masako; Ichihashi, Yukiko; Suzuki, Ayumi; Hayashi, Sakurako; Iinuma, Mitsuo; Azuma, Kagaku; Kubo, Kin-ya
Abstract: Background and objective: Maternal stress during pregnancy is an important factor affecting fetal brain development and leading to behavioral disorders such as spatial learning deficits and inhibition of hippocampal neurogenesis in the offspring. Occlusal disharmony induces cognitive deficits by suppressing hippocampal neurogenesis via increased plasma corticosterone levels. The present study aimed to explore the effects of maternal occlusal disharmony during pregnancy on hippocampal morphology and function in the adult mouse offspring. Design: Occlusal disharmony was induced in pregnant mice during the last week of gestation. Male offspring were raised until 4 months old, and then the Morris water maze was performed as a spatial memory test. Newborn cell proliferation in the hippocampal dentate gyrus was analyzed using 5-bromodeoxyuridine (BrdU) immunohistochemical method in separate groups of mice. Results: Plasma corticosterone concentrations were significantly higher in dam with occlusal disharmony. In the adult offspring, maternal occlusal disharmony not only induced learning deficits, but also suppressed cell proliferation in the hippocampal dentate gyrus compared with control mice. Conclusion: These findings suggest that maternal occlusal disharmony during pregnancy increases plasma corticosterone concentrations in the dam, which leads to learning deficits and suppression of hippocampal cell proliferation in the offspring. Occlusal disharmony in the dam may be a risk factor for cognitive impairment in the offspring.